Tinjauan Singkat Teori Komunikasi; Sejarah, Konsep, Perkembangan, dan Tantangannya - Qorib, Fathul (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. This article is a concise attempt to understand communication theory by exploring its historical origins, conceptual foundations, development trajectory, and challenges of the contemporary era. This article's introduction provides an overview of communication and highlights the role of communication theory in understanding the complexity of human interaction. This research uses a comprehensive literature review to trace the history of the development of communication theory and identify key concepts in the field of communication. In the discussion section, this article explores important theoretical concepts in communication theory, from initial linear models to more complex interactive and transactional models. This research also explains the interdisciplinary nature of communication theory, highlighting how communication theory integrates various fields of study. In modern times, this article describes critical traditions, cultural communication, digital media, the emergence of new media platforms and theoretical gaps that need more attention. The conclusion of this article aims to collect the results, highlight the relevance of communication theory, and suggest directions for improvement and innovation. This article will contribute to a deeper understanding of the historical context of communication theory, new conceptual perspectives, developmental dynamics, and challenges faced today in a changing media landscape. Abstrak. Artikel ini merupakan upaya ringkas untuk memahami teori komunikasi dengan mengeksplorasi asal-usul sejarah, landasan konseptual, lintasan perkembangan, dan tantangan era kontemporer. Pengantar artikel ini memberikan gambaran umum tentang komunikasi dan menyoroti peran teori komunikasi dalam memahami kompleksitas interaksi manusia. Penelitian ini menggunakan tinjauan literatur yang komprehensif untuk menelusuri sejarah perkembangan teori komunikasi dan mengidentifikasi konsep-konsep kunci dalam bidang komunikasi. Pada bagian pembahasan, artikel ini mengeksplorasi konsep-konsep teoretis penting dalam teori komunikasi, mulai dari model linier awal hingga model interaktif dan transaksional yang lebih kompleks. Penelitian ini juga menjelaskan sifat interdisipliner teori komunikasi, menyoroti bagaimana teori komunikasi mengintegrasikan berbagai bidang studi. Di zaman modern, artikel ini memaparkan tradisi kritis, komunikasi budaya, media digital, munculnya platform media baru dan kesenjangan teoritis yang perlu mendapat perhatian lebih. Kesimpulan artikel ini bertujuan untuk mengumpulkan hasil, menyoroti relevansi teori komunikasi, dan menyarankan arah perbaikan dan inovasi. Artikel ini akan berkontribusi pada pemahaman yang lebih mendalam tentang konteks historis teori komunikasi, perspektif konseptual baru, dinamika perkembangan, dan tantangan yang dihadapi saat ini dalam lanskap media yang terus berubah.